A methodological note on the measurement of labor income in Mexico - Campos Vázquez, Raymundo M.; Lustig, Nora; Santillán, Alma S. (Estudios Económicos de El Colegio de México, 2014)
In this methodological note we present a homogeneous measurement of labor income that is comparable over all years. Because the categories included in the definition of labor income have changed over time, an adjustment is necessary. In the measurement of inequality it is important not to include the year-end bonus (aguinaldo) or profit sharing (reparto de utilidades) as labor income. Under this adjusted definition, we find an inequality trend for the age group analyzed that is robust, regardless of whether the measurement is for the prior month or a normalised three-month period. For the prior month measurement, an increase in inequality is found until 1994, followed by a decrease until 2008. In the period 2008-2012, inequality remained relatively constant.